Steve Biko - Wilson, Lindy (Ohio short histories of Africa., 2012)
Steve Biko inspired a generation of Black South Africans to claim their true identity and refuse to be a part of their own oppression. Through his example, he demonstrated fearlessness and self-esteem, and he led a Black student movement countrywide that challenged and thwarted the culture of fear perpetuated by the apartheid regime. He paid the highest price with his life. The brutal circumstances of his death shocked the world and helped isolate his oppressors. This short biography of Biko shows how fundamental he was to the reawakening and transformation of South Africa in the second half of the twentieth century - and just how relevant he remains.